Enolase-like protein present on the outer membrane of Pseudomonas aeruginosa binds plasminogen - Ceremuga, Ireneusz (Springer Netherlands, 2014)
Pseudomonas aeruginosa is one of the pathogenic bacteria which utilize binding of the host plasminogen (Plg) to promote their invasion throughout the host tissues. In the present study, we confirmed that P. aeruginosa exhibits binding affinity for human plasminogen. Furthermore, we showed that the protein detected on the cell wall of P. aeruginosa and binding human plasminogen is an enolase-like protein. The hypothesis that alpha-enolase, a cytoplasmatic glycolytic enzyme, resides also on the cell surface of the bacterium was supported by electron microscopy analysis. The plasminogen-binding activity of bacterial cell wall outer membrane enolase-like protein was examined by immunoblotting assay.